Analysis of Workforce Workload for Production Efficiency Improvement in Sandal Manufacturing Using Workload Analysis and Cardiovascular Load Methods - Hilbram Ramadaniel Setiawan; Jaka Purnama (Telkom University, 2026)
This study aims to analyse workforce workload and determine the optimal number of workers in the sandal production process at UD. Al Athyyah Mojokerto using the Workload Analysis (WLA) and Cardiovascular Load (CVL) methods. The company experiences workload imbalances across several production sections, resulting in bottlenecks and the inability to meet production demand. Average monthly demand reaches 5,000 pairs of sandals, whilst actual production only reaches approximately 4,700–4,800 pairs. Data collection was conducted through direct observation, interviews, and stopwatch time studies in the cutting, sewing, assembly, and finishing sections. The collected data were processed to calculate cycle time, standard time, workload percentage, and cardiovascular load values to evaluate both operational and physiological workload conditions. The results show that several workstations are categorised as overloaded, namely Cutting 1 (124%), Sewing 1 (106%), Sewing 2 (117%), Sewing 3 (108%), Sewing 4 (127%), Assembly 3 (102%), and Finishing 2 (105%). Meanwhile, several other activities were classified as underloaded. The CVL analysis indicates that most workers experience moderate to heavy physical workloads, particularly in the sewing and assembly sections, which may lead to worker fatigue and reduced productivity. Based on the analysis results, additional workers are required in overloaded workstations to achieve a more balanced workload distribution and improve production efficiency. The integration of WLA and CVL methods provides a comprehensive evaluation of workforce conditions and supports workforce planning in labour-intensive manufacturing industries.